Estimated prevalence, incidence and healthcare costs of Sjögren’s syndrome in France: a national claims-based study - Raphaele Seror; Valérie Devauchelle-Pensec; Maxime Beydon; Laurent Chiche; Guillaume Desjeux; Joe Zhuo; Virginie Vannier-Moreau (RMD Open)
Objectives To estimate prevalence, incidence and mortality rates, and annual healthcare costs of primary Sjögren’s syndrome (pSS) and SS associated with other autoimmune disorders (SS+AID) in France.Methods French national healthcare claims-based study within the prospective Système National des Données de Santé database that includes the majority of the French population. An algorithm was developed to identify patients with SS and SS-related healthcare claims were analysed between 2011 and 2018.Results Overall, 23 848 patients with pSS and 14 809 with SS+AID were identified. From 2011 to 2018, the prevalence rate increased slightly for pSS (23–32 per 100000) and SS+AID (16–20 per 100 000), with females comprising 90%–91% and 92%–93% of cases, respectively. The incidence rate of SS per 100 000 persons decreased from 2012 (pSS: 4.3; SS+AID: 2.0) to 2017 (pSS: 0.7; SS+AID: 0.3). Mortality rates per 100 000 persons increased from 2012 to 2018 in patients with pSS (0.2–0.8) or SS+AID (0.1–0.5); mean age of death also increased. Artificial tears and hydroxychloroquine were the most common drug reimbursements. Less than half of patients received annual specialist care from a dentist or ophthalmologist. Healthcare costs associated with SS increased from 2011 to 2018 and exceeded the national estimate of expected costs for chronic diseases.Conclusion In this large French population database study, the low prevalence of pSS confirms that it is an orphan disease. SS is clinically and economically burdensome; these findings may help clinicians better understand routine healthcare received by patients.